Design and preparation of a bioresponsive hydrogel for biomedical application as a wound dressing - Witthayaprapakorn C. (2014)
In this work, the sodium salt of 2-acrylamido-2-methylpropanesulfonic acid (Na-AMPS) was photopolymerised in aqueous solution with ethylene glycol dimethacrylate (EGDM) added as a crosslinking agent and 4,4'-azo-bis(4- cyanopentanoic acid) as the water-soluble photoinitiator. The aqueous solution was poured into a vertical sheet-forming mould consisting of two parallel plates covered with Teflon® sheets as release liners. Spacers were used to control the sheet thickness with a polymer mesh inserted in the middle to strengthen the hydrogel. The hydrogel sheets obtained were of 1.2 ± 0.2 mm thickness and showed good transparency, flexibility and skin adhesion. On immersion in distilled water at 37°C, it was found that the equilibrium water content (EWC) reached 98 ± 1% within 20 mins following which the equilibrium water retention (EWR) in ambient air was 21 ± 1% over a period of about 4 hrs. The water vapour transmission rate (WVTR) was measured at 37 °C and was found to be 82 ± 2 g m-2 hr-1. It is concluded that this Na-AMPS hydrogel sheet has properties which show potential for biomedical use as a wound dressing. © 2008 Trans Tech Publications, Switzerland.